Financial Reporting Practices in the Textile Manufacturing Sectors of Bangladesh - Rouf, Md. Abdur; Hasan, Md. Salim; Ahmed, Alim Al Ayub (ABC Journal of Advanced Research, 2014)
The aim of this study is to examine the factors that influence companies to disclose voluntary information in their annual reports of Textile Manufacturing Companies in Bangladesh. The study is used ordinary least squares (OLS) regression model to examine the relationship between dependent variable and independent variables.  The factors are proportion of independent non-executive directors (INDs), board size, board audit committee, ownership structure, Profitability and firm size. The extent of voluntary disclosure level is measured by using 68 items of information. Data have been taken from annual reports of 21 listed Textile Manufacturing Companies in DSE of Bangladesh-2010. The result shows a positive association between board size and voluntary disclosure and also total assets with voluntary disclosure. In contrast, the extent of voluntary disclosure is negatively related to the ownership structure.